Immunonutrition: facilitating mucosal immune response in teleost intestine with amino acids through oxidant-antioxidant balance - Hissen, Karina L.; He, Wenliang; Wu, Guoyao; Criscitiello, Michael F. (Frontiers in Immunology, 2023)
Comparative animal models generate fundamental scientific knowledge of immune responses. However, these studies typically are conducted in mammals because of their biochemical and physiological similarity to humans. Presently, there has been an interest in using teleost fish models to study intestinal immunology, particularly intestinal mucosa immune response. Instead of targeting the pathogen itself, a preferred approach for managing fish health is through nutrient supplementation, as it is noninvasive and less labor intensive than vaccine administrations while still modulating immune properties. Amino acids (AAs) regulate metabolic processes, oxidant-antioxidant balance, and physiological requirements to improve immune response. Thus, nutritionists can develop sustainable aquafeeds through AA supplementation to promote specific immune responses, including the intestinal mucosa immune system. We propose the use of dietary supplementation with functional AAs to improve immune response by discussing teleost fish immunology within the intestine and explore how oxidative burst is used as an immune defense mechanism. We evaluate immune components and immune responses in the intestine that use oxidant-antioxidant balance through potential selection of AAs and their metabolites to improve mucosal immune capacity and gut integrity. AAs are effective modulators of teleost gut immunity through oxidant-antioxidant balance. To incorporate nutrition as an immunoregulatory means in teleost, we must obtain more tools including genomic, proteomic, nutrition, immunology, and macrobiotic and metabonomic analyses, so that future studies can provide a more holistic understanding of the mucosal immune system in fish.